Margī dar nūr - Kifā'ī, ʻAbd al-Husayn Majīd (Kitābfurūshī-i Zavvār, 1980)
Biography of Muhammad Kāzim, 1839-1911, Iranian religiopolitical leader; includes a collection of writings on his life and works by his contemporaries.